The criminology of wrongful cConviction: a decade later - Leo, Richard A. (Journal of contemporary criminal justice, 2017)
This article reflects on the author’s 2005 article, “Rethinking the Study of Miscarriages of Justice,” which sought to describe what scholars empirically knew at that time about the phenomenon, causes, and consequences of wrongful convictions in America. The 2005 article argued that the study of wrongful convictions constituted a coherent academic field of study and set forth a vision for a more sophisticated, insightful, and generalizable criminology of wrongful conviction. In this current article, the author revisits the ideas first developed in “Rethinking the Study of Miscarriages of Justice” to evaluate what scholars have learned about wrongful convictions in the last decade, and what challenges lie ahead for developing a more robust criminology of wrongful conviction. The article concludes that there have been significant theoretical, methodological, and substantive advances in the last decade, but that a root cause analysis of wrongful convictions has yet to come to fruition and urges empirical scholars to begin to study other sources of error and inaccuracy in the criminal justice system. Scholars should develop a criminology of erroneous outcomes, not just of erroneous conviction. By studying both sets of outcomes, scholars can improve accuracy and reduce errors across the board.